ALTERNATIVE METHODS OF COEFFICIENTS CALCULATION OF LINEAR AND INERTIA RESISTANCES OF WAVE EQUALIZATION OF GAS AND GAZCONDENSATE TO BOTTOM-HOLE OF WELL - Кондрат, Олександр Романович; Рой, Микола Миколайович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The review of existent methods of wave equalization determination of gas or gazcondensate products is offered from a layer, coming from the presence of information weekend and specified on the untraditional going near the decision of this task.